Comparison of direct blood smear methods to detect piroplasms in wandering horses from Midwest Brazil - Arthur M.S.V. Pinto; Verônica L.S. Argenta; Patrícia C. Duarte; Tayná C.M. Fino; Benito Soto-Blanco; Antonio Carlos L. Câmara (Pesquisa Veterinária Brasileira)
ABSTRACT: Equine piroplasmosis is an apicomplexan hemoprotozoan-caused disease that affects equids worldwide. Horses that survive piroplasmosis can become asymptomatic carriers for the rest of their lives. The present study aimed to determine the frequency of piroplasms and to compare three different blood smear tests (jugular, peripheral, and splenic blood) to detect piroplasms in asymptomatic wandering horses seized by the “Secretaria de Estado da Agricultura, Abastecimento e Desenvolvimento Rural do Distrito Federal” (SEAGRI-DF), Midwest region of Brazil. Of the 100 horses evaluated, 38 were diagnosed positive for piroplasm (38%), with the etiological agents found at the jugular blood smear in 11% (11/100) of horses, peripheral blood smear in 13% (13/100), and splenic blood smear in 38% (38/100). Piroplasm-positive horses showed anemia, neutrophilia, and lymphopenia, but the hematological changes did not differ statistically between positive and negative horses. In summary, the stray horses evaluated showed a high incidence of piroplasm (38%). All positive horses presented one of the etiologic agents in the splenic blood, but some did not show the parasite in the jugular blood smear (27/38, 71%) or the peripheral blood smear (25/38, 65.8%). Thus, the splenic blood was shown to be the best sample to determine the presence of piroplasm in wandering horses. As it is a low-cost and easy-to-perform test, it can be included in the routine diagnosis of equine piroplasmosis, helping to monitor the prevalence of piroplasms in places where molecular techniques are not accessible.